2012
DOI: 10.1016/j.str.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Regulates Assembly of the Caspase-6 Substrate-Binding Groove

Abstract: Summary Caspases, a family of apoptotic proteases, are increasingly recognized as being extensively phosphorylated, usually leading to inactivation. To date, no structural mechanism for phosphorylation-based caspase inactivation is available, although this information may be key to achieving caspase-specific inhibition. Caspase-6 has recently been implicated in neurodegenerative conditions including Huntington's and Alzheimer's diseases. A full understanding of caspase-6 regulation is crucial to caspase-6-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…Rather, this suggests that the primary purpose of cleavage is to generate the loop bundle, which functions as an allosteric activator of the mature enzyme. This observation is supported by studies showing that mutations within the loop bundle can alter catalytic activity without altering the structure of the active enzyme, and by the observation that phosphorylation of the loop bundle can regulate activity in C6 (25,30,31).…”
Section: Discussionmentioning
confidence: 78%
“…Rather, this suggests that the primary purpose of cleavage is to generate the loop bundle, which functions as an allosteric activator of the mature enzyme. This observation is supported by studies showing that mutations within the loop bundle can alter catalytic activity without altering the structure of the active enzyme, and by the observation that phosphorylation of the loop bundle can regulate activity in C6 (25,30,31).…”
Section: Discussionmentioning
confidence: 78%
“…Among the apoptotic caspases, caspase-6 is uniquely resistant to X-linked inhibitor of apoptosis protein-mediated inhibition at either the active site or the dimer interface (22), underscoring the fact that regulation of caspase-6 is distinctive. To date, only caspase-6 has been reported to be inactivated by phosphorylation at Ser-257 by ARK5 kinase (2), which allosterically prevents the proper conformation of one of the substratebinding loops (23). The understanding of the unique features of such regulatory pathways improves our ability to utilize caspase-6 as a therapeutic target.…”
mentioning
confidence: 99%
“…To further determine how palmitoylation of CASP6 might affect its processing and activation (Figure 4a), we utilized computational molecular modelling based on the published crystal structures of CASP6. 24,25,[49][50][51][52][53][54][55] Generation of the model of CASP6 required the construction of coordinates of loop 2 (L2), which forms the substrate-binding groove (active site) and is not resolved in any of the several crystal structures available, presumably owing to high flexibility. The structure of CASP6 has a six-stranded β-sheet flanked by five α-helices and two small β-strands.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structure studies of the phospho-mimetic S257D suggested that phosphorylation of S257 inactivates CASP6 through a steric clash with the proline side chain of residue P201 in the L2' loop, 49 causing reorganization of the L2 loop into an inactive position. 59 Indeed, removal of the clashing proline side chain of P201 (P201G) reversed the S257 phosphorylation-mediated inhibition of CASP6 activity, suggesting that steric hindrance was the underlying mechanism of inhibition.…”
Section: Discussionmentioning
confidence: 99%